2011
DOI: 10.1111/j.1365-2729.2010.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's text messaging: abbreviations, input methods and links with literacy

Abstract: This study investigated the effects of mobile phone text-messaging method (predictive and multi-press) and experience (in texters and non-texters) on children's textism use and understanding. It also examined popular claims that the use of text-message abbreviations, or textese spelling, is associated with poor literacy skills. A sample of 86 children aged 10 to 12 years read and wrote text messages in conventional English and in textese, and completed tests of spelling, reading and non-word reading. Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 12 publications
(39 reference statements)
1
40
1
4
Order By: Relevance
“…While exposure to textisms does not have positive impact on children similar to the positive benefits found for adults, such exposure does not have negative impact on spelling ability. Textism usage has also been shown to be positively linked with standard measures of literacy in studies done in the past decade (Wood et al, 2011;Plester et al, 2009;Coe and Oakhill, 2011;Kemp and Bushnell 2011;Kemp, 2010). Plester et al (2009).…”
Section: Crpmentioning
confidence: 99%
See 2 more Smart Citations
“…While exposure to textisms does not have positive impact on children similar to the positive benefits found for adults, such exposure does not have negative impact on spelling ability. Textism usage has also been shown to be positively linked with standard measures of literacy in studies done in the past decade (Wood et al, 2011;Plester et al, 2009;Coe and Oakhill, 2011;Kemp and Bushnell 2011;Kemp, 2010). Plester et al (2009).…”
Section: Crpmentioning
confidence: 99%
“…Coe and Oakhill (2011) found that poorer readers used significantly fewer textisms when composing text messages than better readers. Moreover, Kemp and Bushnell (2011) found that children who could decipher messages written with textisms quickly scored higher in the areas of spelling, reading and non-word reading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces observations ont ainsi mené certains chercheurs à formuler l'hypothèse selon laquelle les jeunes disposeraient d'une double compétence (Cougnon, 2015) ou d'une digraphie (David et Goncalves, 2007) -voire d'une pluricompétence ou d'une plurigraphie -qui permettrait de passer de l'écrit traditionnel à la CEMO comme on passe d'un registre à l'autre (David et Goncalves, 2007). Plusieurs études comparant écrits formel et informel ont révélé que les jeunes pouvaient utiliser nombre de variations graphiques dans leurs SMS ou autres écrits CEMO sans pour autant les reproduire dans des cadres plus formels tels que des dictées ou des travaux universitaires (Asmaak Shafi e et al , 2010 ;Aziz et al , 2013 ;Drouin et Davis, 2009 ;Kemp et Bushnell, 2011 ;Spooren, 2009 ;Volckaert-Legrier et al , 2009). Ces diff érentes observations peuvent être mises en parallèle avec les études de Millet et al (1990) et de Leporcq (2012) sur les attitudes et représentations qui 5 indiquent que les élèves accordent une attention diff érenciée à l'orthographe en fonction de la situation de communication.…”
unclassified
“…En eff et, on retrouve autant des enquêtes concluant que la CEMO a une infl uence négative sur la compétence orthographique des jeunes (Zahid et Mehmood, 2013 ;Tayebinik et Puteh, 2012 ;Dansieh, 2011 ;Rosen et al , 2010), que des études y voyant au contraire un impact positif (Bernicot et al , 2014 ;Wood et al , 2011b ;Wood et al , 2011a ;Plester et al , 2008 ;Bouillaud et al , 2007), et d'autres enfi n qui n'observent aucune corrélation entre ces deux variables (Aziz et al , 2013 ;Kemp et Bushnell, 2011 ;Asmaak Shafi e et al , 2010 ;Drouin et Davis, 2009 ;Spooren, 2009 ;Volckaert-Legrier et al , 2009). …”
unclassified